Toxoplasmosis infection. - Irina Clara Delgado Varela; Carmen Niurka Piña Loyola; Ariel García Borges (Medisur, 2009)
Background: Toxoplasmosis is the most widespread zoonosis worldwide. Its prevalence can double in rural populations in relation to urban populations, and it is different in persons of different races within the same community. Objective: To determine the characteristics of toxoplasmosis infection in Charavalle community, Bermúdez municipality, Sucre State, Venezuelan Republic. Methods: A descriptive, cross-sectional study was developed between April and September 2006. Through observation and interview the primary data on the 343 patients selected through simple sampling was obtained. The studied population was classified according to socio-demographic variables, the serum presence of IgG antibodies anti-Toxoplasma gondii was determine through indirect hemagglutination and the main risk factors l inked to toxoplasmosis infection were identified. Results: There was a prevalence of the age group between 16 and 30 years, mainly females in the Stratum III of socioeconomic level. Serological prevalence rate of antibodies IgG anti-Toxoplasma gondii was 63, 56/100 inhabitants and the most significant risk factors were: cohabitation with dogs and cats, raw vegetables and fruit intake, and no drinkable water intake. Conclusions: Results largely agree with other researches on the same subject.